2014
DOI: 10.5901/mjss.2014.v5n27p1510
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Undergraduate Engineers in Oral Presentations: A Multimodal Approach

Abstract: Global connectedness and digital revolution have reshaped workplace oral communication requirements. Industries today call for engineers with excellent oral communication and presentation skills. In response to this, this research attempts to move from a monomodal to a multimodal approach in teaching oral presentations for undergraduate engineers. The Learning by Design Model (LBDM) by Kalantzis and Cope (2005) is used as a framework in the teaching of oral presentation using a multimodal approach. Findings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Another example of educational research which could provide English language lecturers information about the impact of teaching practice focuses on the use of multimodal approach [23]. The results of the study involving Malaysian undergraduate engineering students revealed that the infusion of various multimodal resources not only enabled learners to adapt new ways of learning but it has also promoted their engagement in oral communication and presentation skills.…”
Section: Using Educational Research To Inform Learning Inquirymentioning
confidence: 89%
See 2 more Smart Citations
“…Another example of educational research which could provide English language lecturers information about the impact of teaching practice focuses on the use of multimodal approach [23]. The results of the study involving Malaysian undergraduate engineering students revealed that the infusion of various multimodal resources not only enabled learners to adapt new ways of learning but it has also promoted their engagement in oral communication and presentation skills.…”
Section: Using Educational Research To Inform Learning Inquirymentioning
confidence: 89%
“…The study linked the use of task-based language teaching activities with Skehan's cognitive approach [25] and Yule's theory of communicative effectiveness [26]. Skehan's work suggests the kinds of tasks that influence language acquisition while Yule's theory provided a basis for the selection of tasks to develop communicative effectiveness [25], [26].Another example of educational research which could provide English language lecturers information about the impact of teaching practice focuses on the use of multimodal approach [23]. The results of the study involving Malaysian undergraduate engineering students revealed that the infusion of various multimodal resources not only enabled learners to adapt new ways of learning but it has also promoted their engagement in oral communication and presentation skills.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oral presentation skills are considered an essential component in the workplace (Omar et al, 2012) where workers are often asked to deliver progress-reports, present proposals, elucidate the output of projects, explain product descriptions to vendors, and conduct oral briefings (Devi, Amir & Krish, 2014). Therefore, in order to maintain a sustainable business, employers look for diligent graduates with sound academic backgrounds and exceptional oratory and presentation skills in English (Devi, Amir & Krish, 2014;Singh & Singh, 2008). At the university education level, oral presentations are an important part of class throughout the world (Alwi & Sidhu, 2013;Campbell, et.…”
Section: Introductionmentioning
confidence: 99%